Ontogenetic shifts in morphology and ecology of eastern Pacific white sharks revealed by computer vision - Alexandra E. DiGiacomo; Samantha Andrzejaczek; Barbara A. Block (PLoS ONE, 2026)
Body size is a fundamental property of animal physiology, growth, and maturation, yet field measurements remain difficult to acquire for large-bodied, highly mobile marine species such as white sharks ( Carcharodon carcharias) . In this study, we integrate aerial and underwater imagery to obtain high-resolution morphometrics of eastern Pacific white sharks remotely in the Monterey Bay National Marine Sanctuary. We develop and validate a computational pipeline leveraging deep learning analysis of Unoccupied Aircraft System (UAS) imagery to extract shark total length and body condition, given by a span-length ratio. UAS-based morphometric data reveal that white sharks form size-structured aggregations aligned with oceanographic gradients, indicating that coastal areas within Monterey Bay function as key transitional zones along a continuum of ontogenetic habitat use on the central coast of California. Across individuals, extended girth-length scaling relationships indicate proportionally greater girth amongst eastern Pacific white sharks relative to other populations. This pattern is particularly pronounced in females, which exhibit progressively higher body condition with life stage, likely reflecting the energetic demands of reproduction or sex-specific foraging strategies. By linking UAS-derived morphometrics to ecological context, this approach enables a novel population-level investigation of ecological structure, body size, and morphological variation in a marine predator population.